Placenta Accreta Spectrum (PAS) Disorders: Lessons Learned from the Introduction of Different Management Strategies in an Australian Tertiary Hospital. Retrospective Study (2004 to 2020) - Rita Caldas; Alexander Parr; Alan Adno; Nira Borok; John Smoleniec; Farhad Rahimpanah (IMR Press, 2023)
Background: Placenta accreta spectrum (PAS) disorder refers to pathologic adherence of the placenta and presents multiple perinatal challenges, accounting for between 30-50% of emergency peripartum hysterectomies. Accurate prenatal diagnosis allows multidisciplinary management and delivery at centres with experience and has been shown to improve perinatal outcomes. This study aims to analyse the results of implementing different strategies across the years on the diagnosis and management of PAS in a tertiary Australian hospital (Liverpool Hospital) including: the use of magnetic resonance imaging (MRI) and the benefits of the use of iliac artery balloons and ureteric stents. Secondary objectives include analysis of the risk factors and outcomes. Methods: Retrospective case series of 34 pregnancies complicated by PAS disorders, diagnosed between 2004 and 2020, and delivered at Liverpool Hospital. Descriptive and analytic study (with a significance level of p ≤ 0.05), approved by the Research Ethics and Governance Information System. Results: The incidence of PAS was 0.6 per 1000 deliveries. The typical risk factors (previous uterine surgeries and placenta praevia) were present in 79% of the cases. MRI was used in 39% of the cases (when ultrasound was inconclusive or placenta posterior) and was only inconclusive in 1 case. In total, 32% required emergency delivery due to haemorrhage or preterm labor. The overall complications rate was 32%. Ureteric stents were used in 44% of the cases and there were no ureteric injuries. The use of iliac balloons reduced the total blood loss (2.5 L compared to 2.8 L), however this difference was not statistically significant (p = 0.21). Conclusions: The prenatal diagnosis of PAS is essential to allow optimal perinatal management of these cases. The use of MRI appears helpful when ultrasound is inconclusive. In our study, the use of iliac balloons reduced blood loss, although this was not statistically significant, and ureteric stents appeared useful to avoid ureteric injury in the most complex cases, although the sample is very small. We hope that our study will help us improving our clinical practice.